Perfiles latinoamericanos: entrevista a Inés Dussel (Latin American Profiles: Interview with Inés Dussel) - Anny Ocoró-Loango; Ruth Amanda Cortés Salcedo (Pontificia Universidad Javeriana, 2010)
No aplica